Greek Immigrant Authors in Germany - Eideneier, Niki (Études helléniques / Hellenic Studies, 2005)
Germany may not be considered a country of immigration but it has certainly been a country of guest workers (Garstarbeiter). Many of these were Greek immigrants who were writers or became writers. Their literature has been called 'immigration literature' among other labels. This article considers the various labels and describes the Greek immigrants active in the literary landscape of Germany and even Greece. The author provides a rare, sweeping overview of the scene from the early post-war period to today.